Interference of Croatian in the Pronunciation of the Twelve Most Frequent RP Consonants - Josipović, Višnja (Array, 1987)
In this paper the author establishes three groups of deviations or errors in the speech of Croatian speakers of English. The first group comprises predictable errors resulting from the basic diferences between the the phonetic and phonological inventories under consideration. The second group, a particularly interesting one, includes some unexpected errors dealt with for the first time in the literature. Notably, here belogs the excessive devoicing of English final obstruents. Finally, it is shown that the cumulative effect of a foreign accent is also created by errors from the third group, manifested as the hypercorrect pronunciation of the target – language consonants.